2015
DOI: 10.1002/2015gl065248
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotail dynamics at Mars: Initial MAVEN observations

Abstract: We report on the complex nature of the induced Martian magnetotail using simultaneous magnetic field and plasma measurements from the Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft. Two case studies are analyzed from which we identify (1) repetitive loading and unloading of tail magnetic flux as the field magnitude changes dramatically, exhibiting signatures similar to substorm activity within intrinsic magnetospheres; (2) multiple current sheet crossings indicative of plasma sheet flapping; (3) tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(93 citation statements)
references
References 48 publications
7
86
0
Order By: Relevance
“…At Mars, observations of magnetic reconnection (Dubinin et al, 2008;Eastwood et al, 2008;Harada et al, 2015aHarada et al, , 2017, flux rope formation (DiBraccio et al, 2015;Eastwood et al, 2012;Hara et al, 2017), current sheet flapping , Marsward and tailward ion flows (Harada et al, 2015b), magnetic lobe dependence on IMF orientation Romanelli et al, 2015) and ionosphere magnetization , and bulk plasma escape (e.g., Brain et al, 2010;Halekas et al, 2016) have been reported in the magnetotail. At Mars, observations of magnetic reconnection (Dubinin et al, 2008;Eastwood et al, 2008;Harada et al, 2015aHarada et al, , 2017, flux rope formation (DiBraccio et al, 2015;Eastwood et al, 2012;Hara et al, 2017), current sheet flapping , Marsward and tailward ion flows (Harada et al, 2015b), magnetic lobe dependence on IMF orientation Romanelli et al, 2015) and ionosphere magnetization , and bulk plasma escape (e.g., Brain et al, 2010;Halekas et al, 2016) have been reported in the magnetotail.…”
Section: 1029/2018gl077251mentioning
confidence: 99%
“…At Mars, observations of magnetic reconnection (Dubinin et al, 2008;Eastwood et al, 2008;Harada et al, 2015aHarada et al, , 2017, flux rope formation (DiBraccio et al, 2015;Eastwood et al, 2012;Hara et al, 2017), current sheet flapping , Marsward and tailward ion flows (Harada et al, 2015b), magnetic lobe dependence on IMF orientation Romanelli et al, 2015) and ionosphere magnetization , and bulk plasma escape (e.g., Brain et al, 2010;Halekas et al, 2016) have been reported in the magnetotail. At Mars, observations of magnetic reconnection (Dubinin et al, 2008;Eastwood et al, 2008;Harada et al, 2015aHarada et al, , 2017, flux rope formation (DiBraccio et al, 2015;Eastwood et al, 2012;Hara et al, 2017), current sheet flapping , Marsward and tailward ion flows (Harada et al, 2015b), magnetic lobe dependence on IMF orientation Romanelli et al, 2015) and ionosphere magnetization , and bulk plasma escape (e.g., Brain et al, 2010;Halekas et al, 2016) have been reported in the magnetotail.…”
Section: 1029/2018gl077251mentioning
confidence: 99%
“…In this study we concentrate on the analysis of the cross‐tail CS that separates two lobes of antiparallel magnetic field of the Martian magnetotail formed by the draped IMF (e.g., Luhmann et al, ). The crossings of the cross‐tail CS are identified by the changes of the polarity of B X field along with the decrease of | B | and the increase of ion β (e.g., DiBraccio et al, ; Dubinin & Fraenz, ; Harada et al, , ).…”
Section: Observationsmentioning
confidence: 99%
“…[] analyzed MAVEN magnetic field and electron data to assess the complex field topology in the tail, suggesting that the Martian magnetotail configuration appears to be a hybrid between induced and intrinsic magnetospheres. MAVEN has also made great progress in terms of the tail plasma dynamics: tailward escape of planetary ions has been observed in the form of plasma clouds [ Halekas et al ., ], detached magnetic flux ropes [ DiBraccio et al ., ; Hara et al ., , ], bulk acceleration due to magnetic reconnection [ Harada et al ., ], and the tailward transport of suprathermal (>25 eV) planetary ions [ Brain et al ., ; Dong et al ., ; Harada et al ., ].…”
Section: Introductionmentioning
confidence: 98%